2004
DOI: 10.1590/s0124-00642004000300004
|View full text |Cite
|
Sign up to set email alerts
|

Efectos del trabajo infantil en la salud del menor trabajador

Abstract: RESUMENObjetivos Revisamos el tema del trabajo infantil, en tres aspectos: 1. Las características de los niños que los hacen vulnerables ante el trabajo; 2. Las enfermedades y accidentes relacionados con el trabajo infantil, y 3. Las lesiones asociadas con diversas ocupaciones de menores, como agricultura, construcción, manufactura, textiles, industria del cuero, ventas en calle y trabajo en plazas de mercado. Métodos Se consultaron las bases de datos Medline, EBSCO, PROQUEST e HINARI, y material de la Organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 80 publications
0
9
0
9
Order By: Relevance
“…Some studies (2,7,8) have described a concern regarding the scarcity or lack of public policies on child labor; likewise, they have noted that the constantly increasing child labor rates seriously affects children and adolescents' development and makes the socioeconomic gap between working and non-working children and adolescents bigger. Similarly, other studies (8)(9)(10)(11)(12) have shown a concern regarding the lack of regulations on child labor.…”
Section: Literature Reviewmentioning
confidence: 83%
See 2 more Smart Citations
“…Some studies (2,7,8) have described a concern regarding the scarcity or lack of public policies on child labor; likewise, they have noted that the constantly increasing child labor rates seriously affects children and adolescents' development and makes the socioeconomic gap between working and non-working children and adolescents bigger. Similarly, other studies (8)(9)(10)(11)(12) have shown a concern regarding the lack of regulations on child labor.…”
Section: Literature Reviewmentioning
confidence: 83%
“…In general, these children and adolescents are unskilled workers who help their families by performing tasks such as the application of fertilizers, agrochemicals and pesticides, which are activities where they are exposed to significant risks. (8) Some factors that have been proposed to be associated with the occurrence of this phenomenon include poverty, cultural aspects, gender differences, the quality of education, family dynamics and the notion that parents have regarding work as a formative process for their children, since it has been culturally accepted that it provides them with a sense of responsibility and autonomy and helps them to achieve emotional maturity. (8,9) A fundamental factor for the occurrence of child labor, especially in rural areas, is that there is not a clear distinction between productive and reproductive labor, and therefore children and adolescents start helping in their household by doing housework or agricultural production tasks from an early age, since in these contexts most of the times education is associated with work and both converge in a unique process.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…7,11,12,16,17 Children working in the streets suffer the consequences of early workforce entry, including workplace abuse and economic exploitation, which can lead to psychological problems. 18 In fact, workplace abuse constitutes one of the most prevalent and potentially lethal hazards faced by children working in the streets. 6,16 Economic exploitation, or using children to obtain money, can also be considered a form of abuse.…”
Section: Introductionmentioning
confidence: 99%
“…work-related injuries occur among children that result in 2.5 million becoming disabled and 32,000 fatalities each year [7]. Working children are more susceptible to harm from exposures than adults [8] [9] and more susceptible to emotional and physical abuse and drug addictions [10] [11].…”
mentioning
confidence: 99%